State of Korean and Overseas Markets for Environment-Friendly Agricultural Products and Challenges 2018 - 정학균 (한국농촌경제연구원, 2018)
 Recently, the acreage of certified environment-friendly agricultural products in South Korea has been stagnant since the slight decrease between 2013 and 2015. – In 2017, although the acreage of certified environment-friendly agricultural products in the country grew by 0.8% year on year, the shipment volume per hectare fell by 13.1% compared with the previous year to 496,400 tons.  The market size of environment-friendly agricultural products in 2017 is estimated at KRW 1 trillion 360.8 billion, a 7.2% decrease from the previous year, because of the decline in the shipment volume despite the slight price increase. The market size of the products is forecasted to reach KRW 2 trillion 136 billion (organic agricultural products KRW 574.5 billion, non-pesticide agricultural products KRW 1 trillion 561.5 billion) by 2025, growing by 5.8% on annual average.  In the world organic food market, because demand is increasing faster than supply, strategies for stable production and export of organic food are necessary. – It is needed to seek strategies for exporting to the US and Europe that account for most consumption of organic food in the world.  To stably supply environment-friendly agricultural products, it is required to develop related technologies and production models for major products. – As the biggest difficulty in converting to environment-friendly agricultural practices is weeds, disease, and insect pest, it is necessary to first develop relevant technologies. – It is needed to develop and disseminate production models for major products.  Because the market size of environment-friendly agricultural products is forecasted to continually grow by 2025, various plans to promote the consumption of the products are required. – Consumers think high prices the biggest difficulty in consumption. Therefore, to decrease the prices of environment-friendly agricultural products, it is necessary to continuously make up for the production cost gap between general farming and environment-friendly farming through direct payment programs, and to continually minimize costs by developing and using cheaper environment-friendly farm materials and equipment at the same time. – To stably secure a market for environment-friendly agricultural products, it is needed to first set up plans to gain consumer trust in the products.  For sustainable agricultural production and incentives for environment-friendly agricultural production, it is required to effectively utilize agri-environment conservation programs that the Ministry of Agriculture, Food and Rural Affairs is planning. – Introducing and expanding these programs will financially support environment-friendly farms and enhance the sustainability of domestic agricultural production. – Also, introducing the programs is expected to be a good opportunity to raise awareness of the environmental value of environment-friendly agricultural production.